The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa - Poltavsky, Alexander N.; Kravchenko, Vasiliy D.; Traore, Mohammed M.; Traore, Sekou F.; Gergely, Petrányi; Witt, Thomas J.; Sulak, Harry; Beck, Robert H.-T.; Junnila, Amy; Revay, Edita E.; Doumbia, Seydou; Beier, John C.; et al. (Zootaxa, 2018)
Seventy-nine taxa of Pyraloidea were collected in 2014 with light traps in the woody savannah zone south of Bamako, Mali. Three taxa out of 79 were identified to genus level only. 78 of the 79 species are new records for Mali, 17 are new for West Africa. Most species (54) belong to the subfamily Spilomelinae (family Crambidae). The majority of observed species have wide distribution areas. The only regional endemic is Hypsopygia bamakoensis (Leraut, 2006). Concerning the biogeographical categories most of the species (34) are Afrotropical, seven species cosmopolitan, and the remaining species occur in the Palaearctics with a preference to the Palaeotropics. The most common species, Patania balteata (Fabricius, 1798) comprised 40.0% of all specimens collected. It is known to be a pest of the mango tree, which is common in the light-trapping area.